2018
DOI: 10.1007/s10493-018-0291-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity within grass-associated Abacarus species complex (Acariformes: Eriophyidae), with the description of a new species, Abacarus plumiger n. sp.

Abstract: Accurate estimation of species richness is often complex as genetic divergence is not always accompanied by appreciable morphological differentiation. In consequence, cryptic lineages or species evolve. Cryptic speciation is common especially in taxa characterized by small and simplified bodies, what makes their proper identification challenging. The cereal rust mite, Abacarus hystrix, was regarded for a long time as a species associated with a wide range of grass hosts, whereas wide host ranges are rather rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…They are known to disperse passively via wind currents or vectors, infest a wide range of grass species (both cultivated and wild) and cause important economic damage to cereal crops (Frost and Ridland 1996 ; Sabelis and Bruin 1996 ; Navia et al 2010 ). Both species also represent complexes of cryptic species, consisting of multiple genetically divergent lineages differing in their host plant ranges (Skoracka et al 2018a ; Laska et al 2018 ). In this study we worked with the CRM complex 2 associated with wheat ( Triticum aestivum ) and quackgrass ( Elymus repens ) (Laska et al 2018 ), and with the most globally distributed WCM lineage (herein MT-1, also known as type 2) associated with cereals (Skoracka et al 2014 , 2017 , 2018b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are known to disperse passively via wind currents or vectors, infest a wide range of grass species (both cultivated and wild) and cause important economic damage to cereal crops (Frost and Ridland 1996 ; Sabelis and Bruin 1996 ; Navia et al 2010 ). Both species also represent complexes of cryptic species, consisting of multiple genetically divergent lineages differing in their host plant ranges (Skoracka et al 2018a ; Laska et al 2018 ). In this study we worked with the CRM complex 2 associated with wheat ( Triticum aestivum ) and quackgrass ( Elymus repens ) (Laska et al 2018 ), and with the most globally distributed WCM lineage (herein MT-1, also known as type 2) associated with cereals (Skoracka et al 2014 , 2017 , 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…Both species also represent complexes of cryptic species, consisting of multiple genetically divergent lineages differing in their host plant ranges (Skoracka et al 2018a ; Laska et al 2018 ). In this study we worked with the CRM complex 2 associated with wheat ( Triticum aestivum ) and quackgrass ( Elymus repens ) (Laska et al 2018 ), and with the most globally distributed WCM lineage (herein MT-1, also known as type 2) associated with cereals (Skoracka et al 2014 , 2017 , 2018b ). Experimental individuals of both species were obtained from laboratory stock colonies reared (each species separately) for several years on wheat in the laboratory of the Faculty of Biology, Adam Mickiewicz University, Poznań, Poland.…”
Section: Methodsmentioning
confidence: 99%
“…complex [73]. Studies of other taxa have reported a range of interspecific and intraspecific distances, but without a gap analysis (e.g., [53,57,74,75]).…”
Section: Modern Taxonomy and Its Role In Improving Classical Biological Control Programsmentioning
confidence: 99%
“…Mites in the superfamily Eriophyoidea, numbering over 5000 species and characterized by their minute size (< 300 µm), relatively simple morphology, and obligate herbivory, are becoming widely recognized as globally adventive or invasive species (Navia et al 2010). Their importance in the fields of agriculture and ecology has grown in the wake of recent significant advancements in microscopy and molecular biology that facilitate improved taxonomic (Navajas and Navia 2009;Monfreda et al 2010;de Lillo et al 2010;Chetverikov et al 2015;Skoracka et al 2015;Laska et al 2018), behavioral (Skoracka et al 2007;Michalska et al 2010;Kiedrowicz et al 2017;Laska et al 2019), and other studies of these tiny, fascinating beasts. Many eriophyoid species have been recorded as agricultural pests, either due to their own feeding or as vectors of plant diseases (Navia et al 2010;de Lillo et al 2018).…”
Section: Introductionmentioning
confidence: 99%